A comparative study between open versus laparoscopic Hartmann reversal: A single-center experience and analysis. Issue 47 (24th November 2021) - Cho, Hye Jung; Kim, Woo Ram; Kim, Jong Woo
Abstract : Abstract: As one of the most challenging procedures in colorectal surgery, Hartmann reversal (HR) carries a burden of morbidity and mortality. We report our experience and compare open and laparoscopic HR. Between December 2012 and January 2020, 30 patients who underwent Hartmann reversal were reviewed. All patients either received laparoscopic or open reversal. Of the 87 patients who underwent Hartmann operation (HO), 30 patients received HR (Laparoscopic Hartmann Reversal, [LHR], n = 20; Open Hartmann Reversal, Open Hartmann Reversal [OHR], n = 10). There were 15 males and 15 female patients. The mean operation time was 223.8 minutes (range 115–350 minutes) with mean blood loss of 252.5 mL (range 0–700 mL). There was no conversion from LHR to OHR, and there was no ileostomy formation. Mean time to flatus was 5.0 days (range 2–13 days). There were 15 early postoperative complications and 5 late postoperative complications, but only 1 case of grade 3A. No anastomosis leakage was reported. HR is an operation that can be performed safely in well-selected patients. Minimally invasive techniques, such as LHR, is an attractive option resulting in shorter operation time, less blood loss, less pain, and shorter hospital stay.